Suuntaa ilmaisevat adverbiaalit, suhdesääntö ja käsin: »ikkunointiin» perustuva analyysi - Ojutkangas, Krista (Virittäjä, 2003)
Directional adverbials, referential relations and the Finnish particle käsin: an analysis based on windowing of attention (englanti) 2/2003 (107) Directional adverbials, referential relations and the Finnish particle ksin: an analysis based on windowing of attention The article describes and discusses the functions of the Finnish directional particle ksin (ksi hand + instructive case-ending) (direction) from in the framework of cognitive linguistics. (The meaning of from in this particle contrasts with the meaning in nouns with an elative or ablative case-ending.) The meaning of the particle ksin in Old Literary Finnish, however, was not (direction) from but (direction) towards, and this reversal of direction in the meaning requires an explanation. A central concept in the analysis used is the process of windowing of attention (Talmy 2000). Windowing is based on peoples ability to focus on selected parts of different event frames, and to foreground and background participants as they choose; windowing also refers to the ways in which this selection is reflected in linguistic descriptions of the events. The writer argues that the functions of this particle in Modern Finnish and the meaning change are motivated by windowing. Furthermore, it is argued that applying an analysis based on windowing can explain why adverbials that express different directions (to vs. from) function differently with respect to the referential relations between spatial adverbials and the core arguments of transitive clauses. In Modern Finnish, the most important function of ksin is to window the location of the agent and to code it as the source of the energy in transitive clauses, i.e. to focus attention on the initiator of the action and on the transmission of energy between the participants of the event. This is a strategy that emphasises agentivity and is supported by other functions of the particle, which also apply to its use with intransitive verbs. These include the contrasting function, how ksin picks one preferred starting point from a group of choices, and the way it turns the starting point into a base camp, a home to which the agent returns between repeated actions in an iterative event. The special connection between agentivity and ksin in the meaning from led to the hypothesis that it would also be the motivation for the change in meaning to > from: the agents role and agentivity are so prominent in human communication that they deserve specialised linguistic expressions. Another key concept in this article is the relation rule, which concerns the referential relations between core arguments and the adverbials inflected in locative cases. According to the general principle formulated by Paavo Siro (1964), an adverbial quasi-predicate [i.e. a case ending or an adposition] modifying a verb [not e.g. a clause] refers, in an intransitive clause, to the subject, and in a transitive clause, to the object. As ksin is used to disambiguate the referential relations in potentially ambiguous contexts, this article continues the discussion of the relation rule in Finnish linguistics that was earlier conducted by Alhoniemi (1975) and Leino (1989). Krista Ojutkangas Kielenainekset ajaa (kieli: suomi, sivulla: 173) altakäsin (kieli: suomi, sivulla: 172) edeltäkäsin (kieli: suomi, sivulla: 172) edes- (kieli: suomi, sivulla: 172) edeskäsin (kieli: suomi, sivulla: 172) koota (kieli: suomi, sivulla: 166-) käsi (kieli: suomi, sivulla: 162) käsin (kieli: suomi, sivulla: 162) määrätä (kieli: suomi, sivulla: 172) päin (kieli: suomi, sivulla: 162) päin (kieli: suomi, sivulla: 173) päin (kieli: suomi, sivulla: 174) päin (kieli: suomi, sivulla: 179) rinnan (kieli: suomi, sivulla: 162) sisältäkäsin (kieli: suomi, sivulla: 172-)